Some Markers of Liver Regeneration in Young Children with Congenital and Chronic Hepatitis - O.G. Shadrin; O.O. Magomedov; N.F. Chernega; N.M. Basaraba; S.V. Dyukareva; A.A. Kovalchuk (Zaslavsky O.Yu., 2014)
As a result of clinical and paraclinical studies in young children with hepatitis we detected increased concentration of hepatocyte growth factor (HGF) and tumor necrosis factor α, which indicates a high fibrous focus of inflammation in the liver, regardless of the duration of the course. Correlation between the levels of HGF and protein-bound hydroxyproline justifies the use of indicators as markers of the regenerative activity of the liver, the relationship between them increases with the duration of the pathological process.